Competition Test Veteran Affairs Medical Centre (VAMC) Score And KIMS-14 For Predicting the Dehiscence of Abdoment Post Laparotomy Operating Wounds - Reza Akmal; Efman EU Manawan; Mgs Irsan Saleh (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2020)
Introduction: Abdominal wound dehiscence (AWD) is a complication of severe postoperative abdominal surgery, with reported death rates ranging from 10% to 45%. Significant mortality, prolonged hospitalization, increased incidence of incisional hernias and reoperations for ruptured stomachs, with costs associated with the community, emphasize the severity of these complications. The VAMC score and KIMS-14 can be used as screening in predicting surgical injury dehiscence Method: This study is a diagnostic test study to assess the sensitivity and specificity of VAMC and KIMS-14 scoring in predicting the occurrence of abdominal wound dehiscence to be performed in surgery outpatient and digestive surgery ward at the General Hospital, Dr. Mohammad Hoesin Palembang in the period March to May 2019. Results: There were 44 subjects that participated in this study. VAMC has a sensitivity value of 87.5% and specificity of 97.2 with an area under curve value of 0.958 with a cut-off of > 10. KIMS 14 has a sensitivity value of 100% and a specificity of 94.4% with an area under curve value of 0.944 with a cut-off of > 5. Conclusion: KIMS-14 is better in sensitivity, but VAMC is more specific to predict dehiscence licensing in patients undergoing intraabdominal surgery.